The Influence of E-WOM and Digital Marketing Patient’ Re-Visits at The Internal Medicine Polyclinic Sebening Kasih Hospital - Nadhila Nur Amalina; Enrico Adhitya Rinaldi; Nurminingsih Nurminingsih (International Journal of Health and Pharmaceutical (IJHP), 2026)
The research problem arose from indications that some nurses experience difficulties in optimally performing their nursing duties, which can impact the quality of patient care. Unequal distribution of professional competence, low motivation due to a lack of recognition and career development, and a high workload due to an imbalance in the nurse-to-patient ratio are suspected to be the main causes of this decline in performance. The purpose of this study was to analyze the influence of professional competence, work motivation, and workload on nurse performance in the inpatient ward of Sebening Kasih Hospital, Pati Central Java Indonesia. This study, a descriptive quantitative study, recruited 42 respondents: nurses working in the in the internal  medicine polyclinic of Sebening Kasih Hospital, Pati, who had worked in the inpatient ward for at least six months, were permanent nurses or active contract nurses, and were willing to participate. The data collected consisted of primary data collected using a questionnaire. The results concluded that professional competence and work motivation had a positive and significant effect on nurse performance in the inpatient ward of Sebening Kasih Hospital, Pati, Central Java Indonesia Workload negatively affected nurse performance. The higher the workload, the lower their performance.